Comparative study of the effects of the fixed functional appliances forsus fatigue resistant device and MARA in treatment of class II malocclusion through lateral cephalograms analysis - Nogueira, Cinthya Quagliato (2019)
Introduction: Since the success of treatment through removable appliances depends mostly of patient cooperation, functional fixed appliances have been widely used in treatment of Class II malocclusion for a huge number of professionals. Objective: The purpose of this study is to analyze the effects of the Forsus Fatigue Resistant Device and to compare the findings with a well-matched group treated with the Mandibular Anterior Repositioning Appliance (MARA) for the correction of Class II malocclusion, and to compare with an untreated Class II malocclusion control group. Methods: The Forsus group was composed of 14 patients. The MARA group was comprised of 18 patients. The untreated control group was composed of 14 patients. Lateral cephalometric radiographs were taken of each subject at the pretreatment (T1) and posttreatment (T2). Posttreatment changes were calculated as T1-T2. Intergroup comparisons regarding treatment changes were performed using repeated measures analysis of variance (ANOVA) followed by Tukeys test. Results: During treatment, the Forsus group showed statistically significant decrease of maxillary protrusion and maxillomandibular sagittal discrepancy in relation to the control group. The MARA group showed statistically significant greater retrusion of maxillary incisors in relation to the Forsus and the control group. Overjet decreased significantly more in the treated groups in relation to the control group. The molar relationship improved significantly more in both treated groups, and both showed more correction than did the untreated control group. Conclusion: The Forsus and MARA associated with fixed appliances effectively correct the Class II malocclusion, mostly by means of dentoalveolar changes and maxillary growth restraint.